Microbiological and Physiochemical Assessment of Corn Meal (Agidi) - Nnenna Jennifer Omorodion; Modebola Victoria OlaIokungbaye (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
Corn meal (Agidi) is a gel-like traditional fermented starchy food item produced from maize, although millet and sorghum can also serve as raw materials. It is known by different names in different localities. A total of 30 corn meal (Agidi) from differentsellers from various communities and comprisingof 15 white and 15 jollof agidi samples fromChoba market in Port Harcourt Rivers State were examined and analyzed using standard microbial techniques. The Total Bacteria count for white (plain) Agidi rangedof 6.30-8.06 logcfu/g. The Staphylococci count for White Agidi samples ranged of6.0–8.2 logcfu/g. The Coliform count ranged of 6.00-7.96 logcfu/g. The results generated from this study exceeded the permissiblelimit for bacteria in food. Bacteria isolated from White agidi include Staphylococcus spp (31.58%) and Enterococcus sp (21.05%). Bacillus sp, (18.42%), Escherichia coli (15.75%) and Klebsiella sp (10.53%). Pseudomonas sp (2.63%). For jollof agidi, the bacterial isolated Staphylococcus spp (30.8%) Bacillus spp (24.6%). Enterococcus sp (20.0%), Escherichia coli (12.3%), Klebsiella sp 7(10.8%) and Pseudomonas sp (1.5%). pH of corn meal ranged from 4 –6, the moisture content ranged from 80% –90%, while the titratable acidity ranged of0.20 –0.40. Proper handling of agidi during production must be taken.